MYSEJAHTERA APP AND THE PRIVACY RIGHTS IN TIMES OF COVID 19: THE LEGAL AND SYARIAH PERSPECTIVES (International Seminar on Syariah and Law (INSLA), 2020)
The year of 2020 marks the most challenging year when a global health crisis due to the outbreak of COVID-19 pandemic worldwide. In Malaysia, the government took an approach by developing a contact-tracing application, known as MySejahtera to assist the government in managing the outbreaks and to enable the Ministry of Health to slow down the spread of the virus. Nevertheless, the technology has raised the data privacy concern where the app requires various users’ personal details to be inserted before the app can be used. Based on qualitative and doctrinal methods, this article examines whether the government can collect personal information of its citizens in times of pandemic, and to what extent such data should be protected. To do, this paper will be focusing on the invasion of the right to privacy by the government from the legal and Syariah perspectives. The finding suggests that in the time of pandemic COVID-19, it is legal for the government to collect confidential information of its citizens based on the concept of public interest (Maslahah ‘Ammah) grounded from the Syariah principle. Alternatively, it is vital to set the timeline and the data should be destroyed at a certain period. It concludes that the contact tracing apps is inevitable and as an essential tool in combating the outbreaks amidst privacy invasion.